Analytica Chimica Acta - Analytica Chimica Acta (Elsevier, 2026)
Analytica Chimica Acta provides a forum for the rapid publication of original research, and critical, comprehensive reviews dealing with all aspects of fundamental and applied modern analytical chemistry.
FI 1.43
Q1
Keywords: Chemistry; Analytical Chemistry; Química analítica; Acuerdos transformativos; Transformative agreements; Metodologías analíticas; Técnicas quimiométricas